Thermodynamic and surface properties of 4-(Undecyloxy) benzoic acid thermotropic liquid crystal by inverse gas chromatography at infinite dilution - Ozcan, Seher; Tas, Selin; Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (TAYLOR & FRANCIS LTD, 2025)
This study utilized 4-(Undecyloxy) benzoic acid liquid crystal as the stationary phase. The phase transition temperatures of the liquid crystal were ascertained using inverse gas chromatography. The phase transition temperatures of 4-(Undecyloxy) benzoic acid liquid crystal were established at 70, 88, 96, and 136 degrees C via the inverse gas chromatography method. The Flory-Huggins interaction parameters ($\chi _{12} \infty$chi 12 infinity) and mole fraction activity coefficients (${\rm \gamma }_1 \infty$gamma 1 infinity) were derived, and the interactions between the liquid crystal-solvent in the thermodynamic domain were examined. Furthermore, the dispersive surface energy ($\gamma _S D$gamma SD) was determined. The $\gamma _S D$gamma SD values ranged from 40.31 to 56.67 mJ/m2 according to the Dorris-Gray method, and from 38.83 to 52.20 mJ/m2 according to the Schultz methodology. Furthermore, the specific free energy, enthalpy, and entropy of solvents on the liquid crystal were ascertained. The acquired data demonstrated an acidic nature ($K_D/K_A = 0.34$KD/KA=0.34) for the surface of 4-(Undecyloxy) benzoic acid liquid crystal.
Keywords: 4-(Undecyloxy) benzoic acid; chromatography; Flory-Huggins; surface properties; phase transitions; 2ND VIRIAL-COEFFICIENTS; PHYSICOCHEMICAL CHARACTERIZATION; IMPERFECTION; Crystallography; Physics